The Empathic Leader - Boda, Tímea (European Scientific Journal, ESJ, 2017)
Managers and their subordinates often have the same aims as their organisation: to be successful, to be content and to develop in a secure environment under good financial conditions. Still, we can often hear that workers do not feel comfortable, they do not have a good mood in their working places. They are not committed and they are not motivated – in such cases they are guaranteed to fail, and so is their organisation. In the operation of an organisation tight deadlines, hard work, not clearly defined functions and the feeling of not being understood result in role conflicts. The task and the responsibility of a leader is to apply a communication culture that is based on honest interest towards his subordinates and on acceptance, that enables the avoidance of unnecessary tensions. Many managers consider active communication with and care of subordinate workers as an unnecessary activity and a sheer waste of time but the Pareto principle applies in this case as well. The empathetic leader is capable of realising his colleagues’ competencies and accepting their personal aims and using them as a tool for the development of the organisation. The empathetic leader is capable to reach that workers experience the success of the organisation as their own success – this gives the organisation motivated and committed people.